Wellspring of motivation and L2 vision in second language acquisition (SLA): sacred texts as source - Lepp-Kaethler, Elfrieda (2013)
This thesis addresses a largely unexplored territory in second language motivation research. Its focus was to account for unusual persistence, effort and success among learners acquiring additional language(s) in conjunction with a sacred or special text. More specifically, the project sought to identify the factors, mechanisms and conditions that contributed to exceptionally high motivation for SLA. The guiding theoretical frameworks were Ushioda's Person-in Context relational theory and Dornyei's L2 Motivational Self System. A qualitative research approach was employed which included a series of in-depth interviews with 20 highly successful language learners. The findings confirmed both Ushioda's and Dornyei's theories. The Person-in-Context relational theory was helpful in understanding the significant role of the wider socio-religious context in which learners lived their lives. In addition, the three core components of the L2 Motivational Self System (Ideal L2 Self, Ought-to L2 Self and the language learning environment) shed light on these important components in the informants' learning trajectories. The research identified an ideal self in the form of a spiritual vision core to the informants' identities. In addition, the L2 vision was identified as inseparable corollary that enabled informants to achieve their spiritual vision. The third key component in the motivational matrix was the sacred text. However, beyond ideal selves, participants envisioned a shared ideal future grounded in imagined faith communities with concerns for broader societal well-being. The shared ideal future took form in the informants' imagination, not only within their lifetime, but beyond, extending to an 'ultimate' environment. The thesis includes implications for motivational researchers, language teachers and learners.